Characterization of carbonation-cured cement paste using X-ray photoelectron spectroscopy. (20th April 2018) - Khoshnazar, Rahil; Shao, Yixin
Highlights: X-ray photoelectron spectroscopy was effective in studying microstructure of cement pastes cured by carbonation. Carbonation curing of the pastes promoted silicate polymerization at the early-age and long-term. Higher polymerization of silicates and accelerated reaction of C2 S increased the strength of the pastes cured by carbonation. C2 S was more reactive with CO2 than C3 S as evident by QXRD. Abstract: X-ray photoelectron spectroscopy (XPS) was used to examine the microstructure of cement pastes following early-age CO2 curing. The samples were hydrated for 18 h, and, then, were exposed to high-purity gaseous CO2 at a pressure of 0.15 MPa for 6 h. They were subsequently hydrated until the age of 28 d. The samples were tested right after the carbonation process at the age of 1 d, as well as after the subsequent hydration. The results were compared with those obtained for the reference cement pastes which were not exposed to the carbonation curing. It was found that the calcium-silicate-hydrate (C-S-H) produced by the early-age carbonation had a more disordered and highly polymerized structure compared to that in the conventionally hydrated cement paste. The subsequent hydration significantly changed this structure, and resulted in the incorporation of additional calcium ions. The improved compressive strengths at both test ages were attributed to the higher polymerization of silicates in the cement pastes due to the early-age carbonation curing. Based on the quantitative X-ray diffraction results, more than 40% of C2 S phase of cement was reacted in early carbonation at the age of 1 d. This accelerated reaction appeared to be a primary mechanism of the higher compressive strength at both early and late ages.